2012
DOI: 10.7439/ijbar.v3i11.754
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Prevalence in Human Immuno-Deficient Virus (Hiv) Infected Patients With and Without Diarrhoea and Its Association With Cd4 T Cells Counts

Abstract: Background & objectives: Intestinal parasitic infections are major cause of diarrhoea in HIV infected individuals. The present study was undertaken to detect intestinal parasites in HIV infected patients with and without diarrhoea and to determine association between enteric parasites and CD4 T cell count. Methods: The study was carried out at Department of Microbiology, Rural Medical College, Loni, India, between September 2010 and August 2012 among consecutively enrolled 127 HIV infected patients presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Various studies from India and other countries have reported high prevalence of intestinal parasites, ranging between 30-60%. 4,20,22,21,23,24 Our results are comparable with the studies conducted by Gupta et al, 21 In the present study, intestinal parasites were seen in 29.57% HIV seropositive patients without diarrhoea (Table 2). Various studies from India and other countries have reported the prevalence of intestinal parasites, ranging between 12-40%.…”
Section: Resultssupporting
confidence: 88%
“…Various studies from India and other countries have reported high prevalence of intestinal parasites, ranging between 30-60%. 4,20,22,21,23,24 Our results are comparable with the studies conducted by Gupta et al, 21 In the present study, intestinal parasites were seen in 29.57% HIV seropositive patients without diarrhoea (Table 2). Various studies from India and other countries have reported the prevalence of intestinal parasites, ranging between 12-40%.…”
Section: Resultssupporting
confidence: 88%